The Relationship between Dimension of Consumption Value and Intention to Purchase of Green Products - Maharum, Siti Munirah; Md Isa, Normalisa; Salahuddin, Norkhazzaina; Saad, Shahrin (Globeedu Group, 2017)
The existence of green products is still new in Malaysia and most consumers still face difficulties purchasing green products when it comes to the product selection process. To date, the number of studies on green purchase intention among Malaysian consumers is still lacking. In response to this, the present study aims to examine the factors that influence purchase intention of green products among young consumers in Malaysia by using the Theory of Consumption Values as the underpinning theory in measuring consumers’ intention. This is a quantitative study whereby convenience sampling was conducted to a total of 382 respondents from Universiti Utara Malaysia (UUM). The findings indicated that emotional and epistemic values are the most influential factors that help young consumers to make the decision in choosing green products compared to other consumption values. A number of recommendations were highlighted and it is hoped that it can assist the concerned parties in improving green purchase intention among Malaysian young consumers.